Topological and algebraic geometry methods in contemporary mathematical physics - Dubrovin B A; Krichever I M; Novikov S P (Cambridge CSP, 2004)
This volume is a classic survey of algebraic geometry and topological methods in various problems of mathematical physics and provides an excellent reference text for graduate students and researchers. The book is divided into three parts: the first part
Keywords: Algebraic geometry; Homotopy topology; Mathematical physics